The sperm-specific K+ channel Slo3 is inhibited by albumin and steroids contained in reproductive fluids - Lorenz, Johannes; Eisenhardt, Clara; Mittermair, Teresa; Kulle, Alexandra E.; Holterhus, Paul Martin; Fobker, Manfred; Boenigk, Wolfgang; Nordhoff, Verena; Behre, Hermann M.; Strünker, Timo; Brenker, Christoph (Frontiers in Cell and Developmental Biology, 2024)
To locate and fertilize the egg, sperm probe the varying microenvironment prevailing at different stages during their journey across the female genital tract. To this end, they are equipped with a unique repertoire of mostly sperm-specific proteins. In particular, the flagellar Ca2+ channel CatSper has come into focus as a polymodal sensor used by human sperm to register ligands released into the female genital tract. Here, we provide the first comprehensive study on the pharmacology of the sperm-specific human Slo3 channel, shedding light on its modulation by reproductive fluids and their constituents. We show that seminal fluid and contained prostaglandins and Zn2+ do not affect the channel, whereas human Slo3 is inhibited in a non-genomic fashion by diverse steroids as well as by albumin, which are released into the oviduct along with the egg. This indicates that not only CatSper but also Slo3 harbours promiscuous ligand-binding sites that can accommodate structurally diverse molecules, suggesting that Slo3 is involved in chemosensory signalling in human sperm.